Outcomes of Single Stage Repair of Open Tear of Achilles Tendon - Mudassar Nazar, Muhammad Waseem Anwar, Shabbir Ahmad, Abul Qayum Baig, Muhammad Imran, Rashid Usman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the outcome of debridement and repair of open achilles tendon tear in a single setting. Material and Methods: In this study, we included 30 patients who presented with open tendon rupture. The study was conducted from June 2021 to Dec 2021 in Islam Medical College Sialkot and CMH Lahore. Each injury was treated with appropriate debridement and primary repair using Pennington’s variation of Kessler’s approach. Surgery was performed in a single sitting, with the paratenon closed circumferentially and plantaris reinforcement applied when an end-to-end repair couldn’t be obtained. Cast was applied below knee for two months. Weight bearing was started at end of three months. Results: Among the 30 patients in this series, all were male with a median age of 37 years and range 18-68 years. The commonest source of injury was agriculture fields in 14 (46.7%) cases, road traffic accidents in 10 (33.3%) cases, play grounds in 4 (13.3%) and Pakistani toilet in 2 (6.7%) case. At 6 months follow-up, there was not a single case of wound infections or wound dehiscence. Mild restriction of range of motion was diagnosed in 23 (76.7%) patients, moderate in 4 (13.3%) patients and severe in 3 (10%) cases. Conclusion: Early debridement and proper repair of the ruptured tendon are critical in the treatment of an open tendoachilles tear. Soft tissue handling and a modified Kessler approach with additional circumferential suturing and paratenon closure provide appropriate strength to the repaired tendon.